Probabilistic coding of length of series with confirmation of repetition and preliminary sorting for compression of halftone images bits - H. K. Al-Bahadily; V. Yu. Tsviatkou; V. K. Kanapelka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
It's proposed an algorithm for probabilistic coding of the lengths of series with confirmation of repetition and preliminary sorting. The efficiency of this algorithm using for compression without loss of bit planes of halftone images is investigated.